Tracing the Atmospheric Input of Seawater-Dissolvable Pb Based on the Budget of 210Pb in the East Sea (Japan Sea) - Seo, Hojong; Kim, Guebuem; Kim, Young-Il; Kim, Intae (Frontiers in Marine Science, 2021)
In order to determine the atmospheric input of 210Pb and seawater-dissolvable Pb in the East Sea (Japan Sea), we measured the concentrations of total 210Pb and dissolved Pb (< 0.2 μm) in seawater and 210Pb and 226Ra in sinking particles. The East Sea is deep (~3700 m) and enclosed by surrounding continents except for the shallow sills (< 150 m). Since the East sea is located off the East Asian continent under the westerlies, the concentrations of 210Pb and dissolved Pb in this sea are significantly affected by terrestrial sources through the atmosphere. The vertical profiles of total 210Pb and dissolved Pb generally showed a surface maximum and then decreased with depth. The concentrations of dissolved Pb in the surface water were 2 and 3 times higher than those in the North Pacific and North Atlantic Oceans, respectively. Using an independent box model (upper 1000 m or 2000 m), we estimate the atmospheric input of 210Pb to be 1.46 ± 0.25 dpm cm-2 y-1, which is within the range of published results from the land-based sites (0.44–4.40 dpm cm-2 y-1) in Korea, China, and Japan. Based on this flux, the residence time of total 210Pb in the East Sea is calculated to be approximately 7.1 ± 1.6 y, which is twice lower than the previous estimation. Combining the residence time of 210Pb and the inventory of dissolved Pb, the atmospheric input of seawater-dissolvable Pb is estimated to be 0.98 ± 0.28 nmol cm-2 y-1. This flux is approximately 25% of the Pb flux through the wet deposition (acid-leachable fraction). Thus, our results suggest that the flux and fate of atmospheric Pb in the ocean can be successfully determined using an accurate mass balance model of naturally occurring 210Pb.